Gold–palladium bimetallic nanoalloy decorated ultrathin 2D TiO2 nanosheets as efficient photocatalysts with high hydrogen evolution activity. Issue 16 (28th April 2015) - Xin, Yongji; Wu, Linen; Ge, Lei; Han, Changcun; Li, Yujing; Fang, Siman
<x xml:space="preserve">Abstract</x> In this work, a novel AuPd bimetallic nanoalloy decorated ultrathin 2D titanium dioxide (TiO2) nanosheet with high H2 evolution activity was prepared via a facile in situ synthesis method.